The Contribution of the Philosophy of Science to Scientific Research and Social Life - Sartika; Shermina Oruh; Andi Agustang (Universitas Muhammadiyah Palu, 2024)
The existence of the philosophy of science becomes crucial in facing the advancements in science and technology, marked by the increasing specialization in various fields. The philosophy of science serves as a theoretical framework and research methodology closely related to the scientific research process. It addresses the essence of science, which forms the basis for logical assumptions (neutralistic ethical doctrines), empirical results, and the limitations of scientific knowledge. This article employs a qualitative approach, utilizing library research by examining relevant literature related to the discussed study. It also incorporates document studies of previous research results associated with the philosophy of science. Data collection involves exploring books, reputable scientific journals, and sources from Google Scholar, digital libraries, and others. Through its ability to test, contemplate, and critique assumptions and scientific methods, the philosophy of science also plays a role as a logical foundation for research methodology. In the context of higher education, the philosophy of science provides a solid foundation for scholarly pursuits, offering a logical basis for research methodology, and enhancing understanding of what is referred to as science. The contribution of the philosophy of science to research methodology not only broadens cognitive horizons but also provides a profound understanding expected to motivate researchers to genuinely engage in their research tasks.